2000
DOI: 10.1554/0014-3820(2000)054[0218:idagli]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding Depression and Genetic Load in Laboratory Metapopulations of the Butterfly Bicyclus Anynana

Abstract: We investigated the effects of inbreeding on various fitness components and their genetic load in laboratory metapopulations of the butterfly Bicyclus anynana. Six metapopulations each consisted of four subpopulations with breeding population sizes of N ϭ 6 or N ϭ 12 and migration rate of m ϭ 0 or m ϭ 0.33. Metapopulations were maintained for seven generations during which coancestries and pedigrees were established. Individual inbreeding coefficients at the F 7 were calculated and ranged between 0.01 and 0.51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…A study on the cricket Gryllodes sigillatus (only males) found an 80% increase in RMR of inbred crickets over that in outcrossed individuals, along with a slight decrease in metabolic rate during forced exercise (79). Elevated levels of oxidative stress have been reported in inbred Drosophila males (80), and other studies have shown reduced lifespan in populations suffering from inbreeding or genetic load (81,82). Reduced mass-specific FMR combined with reduced mass of flight muscles go some way toward explaining the reduced flight activity of PT males in the population cage.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the cricket Gryllodes sigillatus (only males) found an 80% increase in RMR of inbred crickets over that in outcrossed individuals, along with a slight decrease in metabolic rate during forced exercise (79). Elevated levels of oxidative stress have been reported in inbred Drosophila males (80), and other studies have shown reduced lifespan in populations suffering from inbreeding or genetic load (81,82). Reduced mass-specific FMR combined with reduced mass of flight muscles go some way toward explaining the reduced flight activity of PT males in the population cage.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, inbreeding can reduce stress resistance (e.g., Armbruster and Reed 2005), increase susceptibility to parasitic infection (e.g., Stevens et al 1997), negatively affect life history traits such as fecundity (Takaka 1993, Roff 1998, and adult longevity (e.g., van Oosterhout et al 2000). In wild and laboratory populations of the mosquito Aedes geniculatus (Olivier), estimated net replacement rate was negatively affected by inbreeding across three populations (Armbruster et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The low costs of inbreeding for fecundity and survival in S. lineatus suggest a relatively high tolerance to inbreeding at the level of full-sib matings. By contrast, comparable studies of other arthropods commonly demonstrate strong inbreeding depression in fecundity or survival (e.g., Ehiobu et al 1989;Pray and Goodnight 1995;Roff 1998;Van Oosterhout et al 2000;Keller and Waller 2002;Day et al 2003;Henter 2003;Radwan 2003).…”
Section: Inbreeding Experimentsmentioning
confidence: 95%